Pengaruh Sikap Kerja Kecerdasan Emosional Dan Etos Kerja Terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Padang Lawas - Eddi Mirson; Ardiansyah Putra; Evi Novita; Handy Karosse Lini Pohan (Manajemen dan Bisnis, 2022)
This formula research internal issue is how influence work attitude on employees  performance.  How influence of emotional  intellegence on employees  performance. How influence of    work ethic  on employees  performance. How influence of    work attitude,  emotional  intellegence,   and work ethic  on employees  performance. This research target is to for know influence and analyze of   work attitude on employees  performance. For know influence and analyze  of emotional  intellegence on employees  performance. For know influence and analyze   work ethic  on employees  performance. For know influence and analyze  work attitude, emotional  intellegence and work ethic on employees  performance. Sample in this research amount to 30 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of work attitude effect positive and significant on employees  performance.   Emotional  intellegence effect positive and significant on employees  performance.   Work ethic  effect positive and do not significant on employees  performance.  Work attitude, emotional  intellegence,  and work ethic  effect and positive and significant on employees  performance